How much we express love predicts how much we feel loved in daily life - Lindy Williams; Sharon H. Kim; Yanling Li; Saida Heshmati; Joachim Vandekerckhove; Robert W. Roeser; Zita Oravecz (PLoS ONE, 2025)
Feeling and expressing love in daily life are interconnected and perhaps mutually influential experiences. In this study we examined the reciprocal dynamics of feeling and expressing love and its relation to well-being using an ecological momentary assessment design. Over a four-week period, we asked participants (N = 52; 67% Female; 80% White) to report their levels of feeling loved and expressing love six times a day. Using a continuous-time process model, we explored individual differences in inertia (i.e., persistence of a process over time) and cross-influences of felt and expressed love over time. We found that increases in expressing love led to increased feelings of being loved over time; however, increases in felt love did not lead to increases in expressing love. Notably, participants who experienced more persistent feelings of love (that is, greater inertia over time) indicated higher levels of flourishing. These results suggest new avenues for psychological well-being interventions which target increasing loving feelings through encouraging more expressions of love.